Photocatalysis of WO3 nanoplates synthesized by conventional-hydrothermal and microwave-hydrothermal methods and of commercial WO3 nanorods - Jarupat Sungpanich (2018)
Copyright © 2014 Jarupat Sungpanich et al. The degradation of methylene blue (MB) dye by tungsten oxide (WO < inf > 3 < /inf > ) photocatalyst synthesized by the 200°C conventionalhydrothermal (C-H) and 270 W microwave-hydrothermal (M-H) methods and commercial WO < inf > 3 < /inf > was studied under UV light irradiation for 360 min. The photocatalysts were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy, Raman spectrophotometry, and UV visible spectroscopy to determine phase, morphology, vibration mode, and optical property. The BET analysis revealed the specific surface area of 29.74, 37.25, and 33.56 m < sup > 2 < /sup > /g for the C-H WO < inf > 3 < /inf > nanoplates, M-H WO < inf > 3 < /inf > nanoplates, and commercial WO < inf > 3 < /inf > nanorods, respectively. In this research, the M-H WO < inf > 3 < /inf > nanoplates have the highest photocatalytic efficiency of 90.07% within 360 min, comparing to the C-H WO < inf > 3 < /inf > nanoplates and even commercial WO < inf > 3 < /inf > nanorods.